Beyond the Balance Sheet: Gender Diversity, ESG, and Capital Structure as Drivers of Firm Performance in Indonesia and Malaysia - Afifa Nurhanifah; Carolyn Lukita; Sekar Putri Rengganis (Journal of Creative Power and Ambition (JCPA), 2026)
This study investigates the influence of Environmental, Social, and Governance performance and Capital Structure on company profitability (ROA), emphasizing the moderating effect of Gender Diversity. This research applies Panel Least Squares regression on a panel data set of 63 companies from 2019 to 2023, yielding 315 balanced observations. The model examines the direct impacts of ESG, Gender Diversity, and Structural Capital on ROA, along with the interaction effects of Gender Diversity with both ESG and Structural Capital. The results indicate that Gender Diversity and Structural Capital exert significant direct effects on ROA, with Gender Diversity exhibiting a negative correlation and Structural Capital demonstrating an evident negative correlation. Although ESG does not exert a substantial direct influence on profitability, the interaction between ESG and Gender Diversity is both favorable and statistically significant. This suggests that gender diversity serves as a beneficial moderator, amplifying the impact of ESG on ROA. Moreover, gender diversity seems to positively attenuate the adverse link between Structural Capital and ROA, with the interaction term being marginally significant. The results indicate that the advantages of ESG investments depend on the presence of gender-diverse leadership or workforce, providing a vital strategic tool for companies and policymakers.